The knowledge and perception about COVID-19 among three tribal population of Khagrachari hill district, Bangladesh: a community based cross sectional study on ongoing outbreak - Morshed, Mohammad M.; Tripura, Soumik; Hossain, Mohammad A.; Rahman, Mohammad M.; Mahmud, Asif; Somadder, Pratul D. (International Journal Of Community Medicine And Public Health, 2021)
Background: The ongoing pandemic COVID-19 is a new disease that provides a little bit of knowledge. Modern society is getting further information about this pandemic. But the people who are far away from development may not get proper learning and instruction to defect the new virus. Keep this reality in mind, and we aimed via this study to find out the precipitance and knowledge about COVID-19 of the tribal community from Khagrachari district, who are backward and less developed people of Bangladesh. Methods: Simple random sampling method is used for selecting responders. A willing responder was interviewed using a per-developed questioner and 348 responders (Chakma-131, Marma-106 and Tripura-111) across the Khagrachari district. All statistical analyses were done by SPSS version 20. Results: COVID-19 is a viral disease known by 87.0% Chakma, 85.0% Marma and 81.1% Tripura alongside 54.2%, 53.8%, and 60.4% Chakma, Marma Tripura; respectively think that COVID-19 is a deadly disease. Using face masks as a safety measurement about 87% of Chakma, 85% of Marma, and 81.1% of Tripura but using hand sanitizer or shop was slightly low compared to facemask use. Although they were eager to take a vaccine at a particular time, it seems they are not optimistic about the vaccine’s efficacy. Conclusions: Overall, the tribal population has sufficient knowledge about COVID-19 and has a good tendency to maintain proper health hygiene to prevent COVID19 infection.